Pengaruh Likuiditas dan Solvabilitas Terhadap Pertumbuhan Laba pada Perusahaan Transportasi yang Terdaftar di BEI Periode 2009-2018 - Zhumayanjeli Simbolon; Miftahuddin Miftahuddin (Universitas Medan Area, 2021)
The purpose of this study was to determine the effect of liquidity and solvency on profit growth in transportation companies listed on the Indonesia Stock Exchange. The population of this study was taken from the years 2009-2018. The analysis technique used is multiple linear regression with the help of the program Eviews 10. The results obtained after this test are simultaneous liquidity proxied by the current ratio and solvency proxied by the debt to asset ratio and the debt to equity ratio have a significant effect on profit growth. While partially the current ratio has a significant effect on profit growth, the debt to asset ratio also has a significant effect on profit growth. Meanwhile, the debt to equity ratio has no significant effect on profit growth. In this study it is also known that the liquidity proxied by the current ratio and solvency proxied by the debt to asset ratio and debt to equity ratio can influence or explain profit growth by 39.98% and the remaining 60.02% is influenced by other factors.